Asian American Spring Festival 1988 Flyer 07 (SJSU Asian American Studies Department, 2024)
Asian American Spring Festival 1988 events flyer. Cultural Activity, held on Mondays, Tuesday, and Thursday from April 11 to April 21 in the Student Union Amphitheater/Upper Pad. Club Day, held on Tuesday, April 12 in the Umunhum Room. Japanese Animation Nite, held on Tuesday, April 12 in the Umunhum Room. Cultural Food Demonstration, held on Wednesday, April 13 at the Bar-B-Que Pit. Film Festival, held on Wednesday, April 13 in the Morris Dailey Auditorium. Career Panel, held on Thursday, April 14 in the Costanoan Room. Comedy Nite, held on Thursday, April 14 in the Loma Prieta Room. Pacific Film Festival held on Tuesday, April 19 to Thursday, April 21 in the Camera 3 Cinema.